Purchase order for supply & installation of mesh ceiling in the corridors of all floors and in other areas for the BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Harbour Developments & Construction Ltd. for the supply and installation of metal mesh ceiling for Brac University new campus project.